THE RECOVERY OF SME BUSINESSES AMONG THE GROUP OF ENTREPRENEURS WITH DECLINING GROWTH (TURNAROUND) Abstract - สาริบุตร, สลิตตา; หิรัญกิตติ, พิมพา; จตุพัฒน์วโรดม, อัครวัฒน์ (RMUTT Global Business and Economics Review, 2018)
Post to the economic crisis Thailand faced in B.E. 2540, Thailand then paid attention to SMEs and it had formed the Office of Small and Medium Enterprise Promotion (OSMEP), SME Bank and Thai Credit Guarantee Corporation: TCG had supported SMEs in form of Portfolio Approach. It divided SMEs into groups according to the business life cycle which is the group of Pre-start-up, Start-up, Expansion, High Growth, Internationalization and Turn Around. OSMEP has defined the term Turnaround as the group of entrepreneurs with declining growth. It is the group with total incomes in three years reduced more than 20 percent. But according to the recovering theory, “turnaround” refers to “business recovery”. Turnaround covers the meaning of “Decline” in the operational steps of the company follow by recovery process. In B.E. 2559, there are the SMEs corporates that submitted the financial statement in latest four consecutive years for 23,615 companies. From the analysis by using the total income criteria from the latest four years financial statement, it was found that SMEs entrepreneurs in the turnaround group were at 71,170 companies (35.74%) and expected to increase in the years to come. It is considered as the heavy burdens for the government to promote for SMEs, thus, reducing turnover is interesting. An approach to do is to prevent business to fall in declining period. It is suggested by the Thai Credit Guarantee Corporation: TCG that SMEs shall regularly check-up on “business health” to close all vulnerability and to add more confidence in business conducting. It is necessary for the entrepreneurs to turn to pay importance by “prompt” and work on advance financial plan. For some businesses that may face with fluid problem and slowdown, some may face with huge severed which leads to NPL or hold in Credit Bureau. These will even more bring the business to dead end since it means being blacklisted to get loan from the bank to sustain the business and out of chance. It is then important to measure the business health to be able to solve the problem on time. Altman Z-Score is the tool for the company’s financial health check in which has been accepted worldwide. Using the Z-Score (Altman, 1968) to analyze the basis to check the financial health of the company is to evaluate on the possibility of bankruptcy with the benefit from the easy to use tool that gives precisely results. This article then aims to explain the Business Life Cycle, Turnaround recovery, and Altman Z-score as a tool for business health check in which would lead SMEs to remain survive with the higher competitive potential to prompt for the future sustainable competition.